A demonstration that the hippocampus supports both recollection and familiarity - Kirwan, C. Brock (National Academy of Sciences, 2009)
Recognition memory is thought to depend on two distinct processes: recollection and familiarity. There is debate as to whether damage to the hippocampus selectively impairs recollection or whether it impairs both recollection and familiarity. If hippocampal damage selectively impairs recollection but leaves familiarity intact, then patients with circumscribed hippocampal lesions should exhibit the full normal range of low-confidence and high-confidence familiarity-based recognition. High-confidence, familiarity-based decisions are ordinarily accompanied by successful recollection (when memory is intact). However, patients with hippocampal lesions, if recollection is impaired, should frequently experience high-confidence, familiarity-based recognition in the absence of recollection, and this circumstance (termed the “butcher-on-the-bus” phenomenon) should occur more often in patients than in healthy controls. We tested five patients with circumscribed hippocampal damage, asking them to recognize recently studied words as well as to remember the context in which the items were studied. Relative to controls, the patients exhibited no increased tendency to experience the butcher-on-the-bus phenomenon. The simplest explanation of the results is that hippocampal damage impairs familiarity as well as recollection. The same conclusion was suggested when two competing models of recognition memory were used to analyze the data.